2019
DOI: 10.1186/s12862-019-1367-6
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary biogeography of the centipede genus Ethmostigmus from Peninsular India: testing an ancient vicariance hypothesis for Old World tropical diversity

Abstract: BackgroundUnderstanding the relative influence of vicariance and dispersal in shaping Old World tropical biodiversity remains a challenge. We aimed to infer the roles of these alternative biogeographic processes using a species time-tree for the centipede genus Ethmostigmus from the Old World tropics. Additionally, we explored fine-scale biogeographic patterns for an endemic radiation of Ethmostigmus from the peninsular Indian Plate (PIP), an area with complex geological and climatic history.ResultsDivergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 72 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The group has a Western Ghats origin with two independent dispersals into Sri Lanka and two independent dispersals into the dry zone in the late Oligocene–early Miocene, with a recent dispersal to SE Asia from Sri Lanka. Our lack of sampling from the Western Ghats and especially the southern Western Ghats precludes analyses of the origins of the genus within the Western Ghats—though many ancient lineages in peninsular India have southern Western Ghats origins (e.g., Grismer et al., 2016; Joshi & Edgecombe, 2019; Joshi & Karanth, 2011; Prasad, Farooqui, Tripathi, Garg, & Thakur, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The group has a Western Ghats origin with two independent dispersals into Sri Lanka and two independent dispersals into the dry zone in the late Oligocene–early Miocene, with a recent dispersal to SE Asia from Sri Lanka. Our lack of sampling from the Western Ghats and especially the southern Western Ghats precludes analyses of the origins of the genus within the Western Ghats—though many ancient lineages in peninsular India have southern Western Ghats origins (e.g., Grismer et al., 2016; Joshi & Edgecombe, 2019; Joshi & Karanth, 2011; Prasad, Farooqui, Tripathi, Garg, & Thakur, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Biju and Bossuyt (2003) revealed that the frog genus Nasikabatrachus (Sooglossidae), endemic to the Western Ghats, is a Gondwanan relict, thus establishing an older biotic link between the Indian subcontinent with Seychelles to the early Cretaceous. Similarly, a recent study by Joshi and Edgecombe (2019) suggest the evolutionary history of Peninsular Indian centipede Ethmostigmus (Scolopendridae) was shaped by the Gondwanan breakup. Most of the biogeographic studies in the last decade within Peninsular India have focused mainly on faunal components (e.g., Agarwal and Karanth, 2015;Bossyut and Milinkovitch 2001;Datta-Roy et al, 2012;Bansal and Karanth, 2010) whereas the biogeography of floral elements remains relatively under explored.…”
Section: Introductionmentioning
confidence: 85%
“…Among the centipede genera studied here, in India, Digitipes is restricted to the wet forests of the Western Ghats, while Ethmostigmus lineages have dispersed to wet forests in the Eastern Ghats in the past (Joshi & Edgecombe, 2019) and Rhysida is widely distributed across different habitat types throughout peninsular India. Our species distribution models predict ranges of E. tristis, R. konda (both of which are Eastern Ghats endemics) and the more widespread R. trispinosa, which extend into the eastern boundary of the Western Ghats.…”
Section: Directions For Centipede Distributions Within and Outside Thmentioning
confidence: 99%
“…50 Ma. As a result, the WG harbours taxa with both Gondwanan and Asian affinities as well as many endemic radiations (Bossuyt & Milinkovitch, 2001;Gower et al, 2011;Joshi & Edgecombe, 2019;Joshi & Karanth, 2011;Surveswaran et al, 2020). In addition, peninsular India also experienced massive volcanic activity during the Cretaceous (ca.…”
Section: Introductionmentioning
confidence: 99%